A study on envy in the Peruvian workplace - León-Donayre, Ramón (2002)
This research explores the presence of envy in the Peruvian workplace through a survey applied to 167 persons (69 men, 98 women, ages between 21 and 55 years old). The surveyed had to provide an evaluation of envy in the workplace and in Peruvian society. Additionally, they had to evaluate the envy they could produce in others and indicate how would they react upon learning that they were envied. Results show that there is a high rate of envy in the workplace and in Peruvian society as well, particularly among women. Inability to acknowledge others’ merits, and badmouthing working colleagues were among the most significant expressions of envy